Development and validation of a 1.5 T MR‐Linac full accelerator head and cryostat model for Monte Carlo dose simulations. Issue 11 (8th October 2019) - Friedel, M.; Nachbar, M.; Mönnich, D.; Dohm, O.; Thorwarth, D.
Abstract : Purpose: To develop, implement, and validate a full 1.5 T/7 MV magnetic resonance (MR)‐Linac accelerator head and cryostat model in EGSnrc for high precision dose calculations accounting for magnetic field effects that are independent from the vendor treatment planning system. Methods: Primary electron beam parameters for the implemented model were adapted to be in accordance with measured dose profiles of the Elekta Unity (Elekta AB, Stockholm, Sweden). Parameters to be investigated were the mean electron energy as well as the Gaussian radial intensity and energy distributions. Energy tuning was done comparing depth dose profiles simulated with monoenergetic beams of varying energies to measurements. The optimum radial intensity distribution was found by varying the radial full width at half maximum (FWHM) and comparing simulated and measured lateral profiles. The influence of the energy distribution was investigated by comparing simulated lateral and depth dose profiles with varying energy spreads to measured data. Comparison of simulations and measurements was performed by calculating average and maximum local dose deviations. The model was validated recalculating a clinical intensity‐modulated radiation therapy plan for the MR‐Linac and comparing the resulting dose distribution with simulations from the commercial treatment planning system Monaco using the gamma criterion. Results: Comparison of simulated and measured data showed that the optimum initial electron beam for MR‐Linac simulations was monoenergetic with an electron energy of (7.4 ± 0.2) MeV. The optimum Gaussian radial intensity distribution has a FWHM of (2.2 ± 0.3) mm. The average relative deviations were smaller than 1% for all simulated profiles with optimum electron parameters, whereas the largest maximum deviation of 2.07% was found for the 22 × 22 cm 2 cross‐plane profile. Profiles were insensitive to energy spread variations. The IMRT plan recalculated with the final MR‐Linac model with optimized initial electron beam parameters showed a gamma pass rate of 99.83 % using a gamma criterion of 3%/3 mm. Conclusions: The EGSnrc MR‐Linac model developed in this study showed good accordance with measurements and was successfully used to recalculate a first full clinical IMRT treatment plan. Thus, it shows the general possibility for future secondary dose calculations of full IMRT plans with EGSnrc, which needs further detailed investigations before clinical use. Abstract :